2015
DOI: 10.1177/0890334415586406
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Patterns in Preterm Infants Born at 28-33 Gestational Weeks

Abstract: Mothers reported large variations in breastfeeding patterns, with higher median breastfeeding session frequencies than previously described in term infants in affluent settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
(85 reference statements)
0
13
0
1
Order By: Relevance
“…Breastfeeding schedules are the norm on hospital wards that care for late preterm infants. Research has shown that mothers continue to breastfeed according to those schedules when the infant grows older . This may have caused a discrepancy between the infants’ behaviour and mothers’ expectations, making it difficult to interpret her infants’ lactation behaviour, resulting in lower breastfeeding self‐efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Breastfeeding schedules are the norm on hospital wards that care for late preterm infants. Research has shown that mothers continue to breastfeed according to those schedules when the infant grows older . This may have caused a discrepancy between the infants’ behaviour and mothers’ expectations, making it difficult to interpret her infants’ lactation behaviour, resulting in lower breastfeeding self‐efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The cohort of preterm infants was followed up to one year of corrected age. Previous data from this cohort have been published and include the extent of the parents' practices of skin‐to‐skin contact and the mothers' and fathers' experiences of KMC , including the support they received for feeding and breastfeeding, and the infants' breastfeeding patterns .…”
Section: Methodsmentioning
confidence: 99%
“…(b) Exclusively and partially breastfed preterm infants with human milk feeding frequency across postnatal ages superimposed on term infant data. Data are presented from a single study by Oras et al () and as median number of feeds per day…”
Section: Resultsmentioning
confidence: 99%
“…For daily frequency of feeds, a weighted mean of 7.7 feeds/day can be used for EBF term infants across all ages. The data from Oras et al () provided context in preterm infant milk intake feeding frequencies, however, more data are needed to inform the frequency of feeds in this population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation